The morphological, clinical, and prognostic factors in the management of giant anterior communicating artery aneurysms: A systematic review of cases - Roua Nasir; Midhat e Zahra Naqvi; Salaar Ahmed; Maarij ul Hassan; Rabeet Tariq; Saad Akhter Khan; Pia Koeskemeier; Rajiv K. Khajuria; Mohammad Hamza Bajwa; Sajjad Muhammad (Brain and Spine)
Introduction: Giant intracranial aneurysms (GIAs) of the anterior communicating artery (AComm) are rare and challenging to treat due to their distinct angioarchitecture. Research question: To review demographic, morphological, clinical, and prognostic factors in the treatment of giant AComm aneurysms to inform decision-making. Materials and methods: Medline, Scopus, and Cochrane databases were searched for records examining cases diagnosed with giant AComm aneurysms. The study type, sample size, patient age, aneurysm site, aneurysm size, presenting complaints, and treatment modality were tabulated, and methodological quality was assessed. Additionally, two cases from our institution were included. Results: The data from 24 retrieved records, including 45 cases (60% treated with direct clipping/clip reconstruction, 20% with surgical bypass±trapping, and 16% with endovascular/combined methods) were obtained. The mean age was 52 years with an overall male preponderance (3:1). 73% presented with symptoms; mostly visual impairment/loss and subarachnoid hemorrhage. 82% had favorable outcomes (mRS 0–2). 56% had a mean maximum diameter between 25 and 30 mm. Cases treated by direct clipping/reconstruction were primarily ruptured, while cases treated by surgical bypass/trapping were unruptured or asymptomatic. Endovascular/combined methods were utilized for only few cases. Discussion and conclusion: Immediate suspicion is warranted for visual impairment with headaches in adults or seizures in the elderly. Direct clipping is the first-line treatment for ruptured cases closely followed by surgical bypass and trapping for unruptured cases. There is limited data on endovascular/combined methods. Evidence from case reports/series should be interpreted with caution. Both inter-modality and intra-modality nuances exist.